Robust design of composites based on weight minimization and uncertainty - Carlos Alberto Conceição António (2014)
A robust design optimization approach for minimum weight and safe shell composite structures with minimal variability in the structural response under uncertainties is proposed in this paper. The uncertainty propagation quantification based on sensitive analysis is performed with the objective of a robustness assessment. After a bi-objective optimization is performed considering the following objective functions: 1) a function which describes the performance or cost of the system; 2) a function which describes the robustness of the system related with uncertainties in input parameters. The multi-objective optimization search is based on a genetic algorithm using dominance concepts. At the end of the optimization process the Pareto front representing the frontier of the trade-off between the "performance" and the "robustness" functions is obtained. The weight and the determinant of the variance-covariance matrix of the response of composite structures are considered as performance and robustness functions, respectively, subject to constraints associated with the structural behaviour. The results obtained considering different concepts of robustness for the same cost function are compared. This bi-objective optimization is a powerfull tool to help designers to make decision establishing the priorities between performance and robustness. (c) Civil-Comp Press, 2014.